Seventy seven (77) questions and answers in costing - Oluwi, G.B. (Ibadan, Nigeria Onibonoje Press, 1990)
The questions and answers are compiled to satisfy the demand and need of undergraduates of Higher Institutions. In preparing the questions and answers, attempts had been made to select areas where students find most difficult
osc 25/08/2021
Loans
Keywords: Cost accounting